Tumor-responsive mitochondria-targeted DON prodrugs for selective glutamine metabolism inhibition - Taejung Kim; Seungseok Oh; Eunbin Jang; Jang Su Jeon; Min-Jun Baek; Dayeon Song; Seohyeon Kang; Seokwon Jeong; Yun Seok Kim; Minkyung Kim; Hayon Kim; Ji-Yoon Lee; et al. (Chemical Engineering Journal, 2026)

Engineering a sustainable dry recycling route for Li battery cathode scrap via the infrared and ultraviolet laser-induced surface modification - Chan Mi Jeon; Jimin Kwon; Jihyeon Bae; Taeyeon Cho; Sooyeon Yang; Seungho Woo; Chaewon Lim; Minseon Sim; Jin Soo Kang; Kyungjung Kwon (Chemical Engineering Journal, 2026)

NEK2 is essential for spindle assembly checkpoint regulation and cytoskeleton organization in porcine oocyte meiotic maturation - Se-Been Jeon; Pil-Soo Jeong; Hyo-Gu Kang; Ji Hyeon Yun; Se-Yeon Eom; Na-Gyeom Oh; Yeounsun Oh; Seung Hwan Lee; Sun-Uk Kim; Seong-Keun Cho; Bo-Woong Sim (Molecular and Cellular Biochemistry, 2026)
NIMA-related kinase 2 (NEK2) is a serine/threonine kinase that plays crucial roles in cellular events such as centrosome separation, cell cycle progression, spindle assembly checkpoint (SAC) regulation, and microtubule stabilization. However, its regulatory function during oocyte meiotic maturation remains unclear. In this study, NEK2 activity was inhibited using the specific inhibitor MBM-55 to evaluate its role in oocyte meiotic maturation and early embryonic development. NEK2 depletion impaired multiple indicators associated with oocyte maturation and decreased the maturation rate. Mechanistic analysis suggested that NEK2 inhibition altered spindle organization and chromosome alignment, which may be associated with impaired kinetochore–microtubule (K–MT) interactions and altered SAC-associated signaling, collectively contributing to MI-stage arrest and increased aneuploidy. In addition, NEK2 deficiency impaired the actin network, reducing spindle migration, preventing the efficient repair of accumulated DNA damage and ultimately leading to apoptosis. NEK2 inhibition in oocytes reduced subsequent embryonic developmental competence, leading to a lower blastocyst formation rate. These findings demonstrate that NEK2 is a critical regulator of porcine oocyte meiotic maturation through its roles in SAC regulation, K–MT attachment, cytoskeletal dynamics, and the DNA damage response.

Formation processes and quality evaluation of natural zeolite deposits in dynamic diagenetic systems of the Janggi Basin, southeastern Korea: implications for zeolite ore exploration - Changyun Park; Hae-in Lee; Jae-Hwan Kim; Donghoon Chung; Yongmoon Lee; Soojin Lee; Tae-Hee Koo; Insung Kang; Ho Sim; Woohyun Choi; Sung Man Seo (Mineralium Deposita, 2026)

Coupling urea wastewater treatment with hydrogen production using interface-engineered copper oxide–graphitic carbon catalysts - Krishnan Veeramani; Subramani Surendran; Dongin Choi; Chanmin Jo; Yoongu Lim; Dae Jun Moon; Gyoung Hwa Jeong; Dongjin Lee; Hyojung Bae; Kwang Ho Lee; Hyunjung Park; Hee Jung Park; et al. (Environmental Research, 2026)

Acrylamide-induced oxidative stress triggers organelle dysfunction, DNA damage, and apoptosis in porcine embryo development - Na-Gyeom Oh; Se-Been Jeon; Hyo-Gu Kang; Eun Young Choi; Se-Yeon Eom; Ji Hyeon Yun; Sun-Uk Kim; Bo-Woong Sim; Pil-Soo Jeong; Seong-Keun Cho (Chemico-Biological Interactions, 2026)

Melatonin safeguards against butylparaben-induced oxidative stress, DNA damage, microtubule instability, and organelle dysfunction during porcine oocyte maturation - Pil-Soo Jeong; Se-Been Jeon; Hyo-Gu Kang; Ji Hyeon Yun; Eun Young Choi; Sun-Uk Kim; Bo-Woong Sim (Journal of Hazardous Materials, 2026)

Zincophilic ultrathin Zn metal anode enabling uniform deposition and corrosion suppression in aqueous zinc ion batteries - Jong Chan Choi; Da-Eun Hyun; Jae Sol Sim; Inuk Lee; Yun Chan Kang (Chemical Engineering Journal, 2026)

Associations of pre- and postnatal levels of three heavy metals with visual impairment in 3-year-old children - Dajeong Ham; Sung Yeon Kim; Sanghyuk Bae; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; JungHeum Jo; A-Ra Jung; Seung Do Yu; Hyun Jeong Kim; et al. (Environmental Research, 2025)

Characterization of formaldehyde-induced hepatotoxicity based on proteometabolomic analysis - Sanjita Paudel; Hyunchae Sim; Eunjoo Kang; Minseo Kim; Chai Won Park; Ann-yae Na; Eun Ki Min; Ki-Tae Kim; Wonhwa Lee; Sangkyu Lee (Toxicology Letters, 2025)

Enhancing embryonic and full-term development during mouse cloning through post-activation treatment with JNJ-7706621 - Hyo-Gu Kang; Min Ju Kim; Ji Hyeon Yun; Eun Young Choi; Se-Been Jeon; Pil-Soo Jeong; Bong-Seok Song; Ki-Hoan Nam; Sun-Uk Kim; Min Kyu Kim; Bo-Woong Sim (Theriogenology, 2025)

Scalable electrodeposition method to construct zincophilic 3D Cu nanosheet current collector for Zn metal anode - Da-Eun Hyun; Jong Chan Choi; Jae Sol Sim; Ki Beom Kim; Yoon Ho Kim; Dae Soo Jung; Yun Chan Kang (Chemical Engineering Journal, 2025)

Correlation analysis between sensory evaluation (QIM) and scientific evaluation during storage of mackerel - Jiyoung Shin; Junho Yang; Sora Lee; Yikang Sim; Seokwon Kang; Hnin OoHlaing; Ji-Young Yang (Food and Humanity, 2024)

In-situ analysis of water transport properties through a reinforced composite membrane in polymer electrolyte membrane fuel cells - Jiwoong Kim; Sehyeon Kim; Seong-Yong Woo; Hyunsoo Chun; Jaebong Sim; Sanggyu Kang; Kyoungdoug Min (Chemical Engineering Journal, 2024)

Validation of a laboratory craving assessment and evaluation of 4 different interventions on cravings among adults with overweight or obesity - Ellen K. Pasquale; David R. Strong; Dawn M. Eichen; Carol B. Peterson; D. Eastern Kang-Sim; Kerri N. Boutelle (Appetite, 2024)

Chemical recovery of a fish farm in Jinju Bay of South Korea after cessation of long-term fish farming - Bo-Ram Sim; Hyung Chul Kim; Sungchan Kang; Sang-Pil Yoon; Dae In Lee; Won-Chan Lee (Ocean & Coastal Management, 2024)

Development of biomarkers to distinguish different origins of red seabreams (Pagrus major) from Korea and Japan by fatty acid, amino acid, and mineral profiling - Junho Yang; Jiyoung Shin; Yikang Sim; Sora Lee; Seokwon Kang; Hnin Oo Hlaing; Ji-young Yang (Food Research International, 2024)

Rapid and facile preparation of freestanding dense polymer membranes from high-boiling-point solvents for anion exchange membrane water electrolyzers - Du Ru Kang; Gi Hyo Sim; So Youn Lee; Jae Hun Lee; Ki Chul Kim; Jong Hak Kim (Chemical Engineering Journal, 2024)

Cadmium exposure impairs oocyte meiotic maturation by inducing endoplasmic reticulum stress in vitro maturation of porcine oocytes - Min-Ah Gwon; Min Ju Kim; Hyo-Gu Kang; Ye Eun Joo; Se-Been Jeon; Pil-Soo Jeong; Sun-Uk Kim; Bo-Woong Sim; Deog-Bon Koo; Bong-Seok Song (Toxicology in Vitro, 2023)

Three-dimensional label-free visualization of the interactions of PM2.5 with macrophages and epithelial cells using optical diffraction tomography - Wang Sik Lee; Inha Kang; Sung-Jin Yoon; Hyunjung Kim; Yugyeong Sim; Youngjun Park; Jinah Park; Jinyoung Jeong (Journal of Hazardous Materials, 2023)

Toward reducing the immunogenic potential of wheat flour: identification and characterization of wheat lines missing omega-5 gliadins encoded by the 1D chromosome - Sewon Kim; Jae-Ryeong Sim; Yong Q. Gu; Susan B. Altenbach; Sandra Denery-Papini; Florence Pineau; Olivier Tranquet; Yu-Jeong Yang; Eun Ji Park; Sun-Hyung Lim; Chon-Sik Kang; Changhyun Choi; et al. (Theoretical and Applied Genetics, 2023)

Chemical profiling of insect-resistant rice shows that geographical variations produce greater differences in chemical composition than genetic modifications - Ji Eun Sim; Sung-Dug Oh; Ye Jin Kim; Soon Kil Ahn; Jaehyuk Choi; Soo-Yun Park; Soon Ki Park; Tae Jin Kim; Kiyoon Kang; Jae Kwang Kim (Plant Biotechnology Reports, 2023)

Adults with overweight or obesity use less efficient memory strategies compared to adults with healthy weight on a verbal list learning task modified with food words - Dawn M. Eichen; Dong-Jin E. Kang Sim; Sara L. Appleton-Knapp; David R. Strong; Kerri N. Boutelle (Appetite, 2023)

Gradational anionic redox enabling high-energy P2-type Na-layered oxide cathode - Seokjin Lee; Wonseok Ko; Hyunyoung Park; Yongseok Lee; Jungmin Kang; Jinho Ahn; Sangyeop Lee; Eunji Sim; Kyuwook Ihm; Kyu-Young Park; Jongsoon Kim (Chemical Engineering Journal, 2023)

Comparison of the pathogenicity of porcine reproductive and respiratory syndrome virus (PRRSV)-1 and PRRSV-2 in pregnant sows - Chang-Gi Jeong; Salik Nazki; Seung-Chai Kim; Amina Khatun; Yun-Hee Noh; Dong-Uk Lee; Sang Chul Kang; Byoung-Joo Seo; Myeon-Sik Yang; Sim-In Lee; In-Joong Yoon; Bumseok Kim; et al. (Archives of Virology, 2022)

Preparation and Characterization of a Lutein Solid Dispersion to Improve Its Solubility and Stability - Chaemin Lim; Jin Kook Kang; Chan Eun Jung; Taehoon Sim; Jaewon Her; Kioh Kang; Eun Seong Lee; Yu Seok Youn; Han-Gon Choi; Kyung Taek Oh (AAPS PharmSciTech, 2021)

Preparation of Gastro-retentive Tablets Employing Controlled Superporous Networks for Improved Drug Bioavailability - Thi Ngoc Le; Jaewon Her; Taehoon Sim; Chan Eun Jung; Jin Kook Kang; Kyung Taek Oh (AAPS PharmSciTech, 2020)

Therapeutic Effects of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells Combined with Cartilage Acellular Matrix Mediated Via Bone Morphogenic Protein 6 in a Rabbit Model of Articular Cruciate Ligament Transection - Hyo-Jin Jeon; Kyung-Ae Yoon; Eun Suk An; Tae-Wook Kang; Yun-Beom Sim; Jongchan Ahn; Ehn-Kyung Choi; Seunghee Lee; Kwang-Won Seo; Yun-Bae Kim; Kyung-Sun Kang (Stem Cell Reviews and Reports, 2020)

Protective effect of Lactobacillus casei HY2782 against particulate matter toxicity in human intestinal CCD-18Co cells and Caenorhabditis elegans - Joo Yeon Kim; So Young Lee; Seung-Hee Jung; Mi Ri Kim; Il-Dong Choi; Jung-Lyoul Lee; Jae-Hun Sim; Cheol-Ho Pan; Kyungsu Kang (Biotechnology Letters, 2020)

Altered intra- and inter-hemispheric functional dysconnectivity in schizophrenia - Yuan Zhang; Zhongxiang Dai; Yu Chen; Kang Sim; Yu Sun; Rongjun Yu (Brain Imaging and Behavior, 2019)

Cinnamomum camphora Leaves Alleviate Allergic Skin Inflammatory Responses In Vitro and In Vivo - Na-Jin Kang; Sang-Chul Han; Seok-Hyun Yoon; Jae-Yeop Sim; Young Hee Maeng; Hee-Kyoung Kang; Eun-Sook Yoo (Toxicological Research, 2019)

Characterization of transgenic mice expressing EGFP under the control of the monkey 20α-hydroxysteroid dehydrogenase promoter - Chae-Won Park; Seong-Keun Jeong; Tsevelmaa Nanjidsuren; Munkhzaya Byambaragchaa; Myung-Hwa Kang; Bo-Woong Sim; Kwan-Sik Min (Science China Life Sciences, 2018)

Cellular growth and fatty acid content of Arctic chlamydomonadalean - Woongsic Jung; Eun Jae Kim; Suyoun Lim; Hyunji Sim; Se Jong Han; Sanghee Kim; Sung-Ho Kang; Han-Gu Choi (Algae, 2016)

A novel and highly specific phage endolysin cell wall binding domain for detection of Bacillus cereus - Minsuk Kong; Jieun Sim; Taejoon Kang; Hoang Hiep Nguyen; Hyun Kyu Park; Bong Hyun Chung; Sangryeol Ryu (European Biophysics Journal, 2015)

Proof-of-concept randomized controlled trial of pregnenolone in schizophrenia - Christine E. Marx; Jimmy Lee; Mythily Subramaniam; Attilio Rapisarda; Dianne C. T. Bautista; Edwin Chan; Jason D. Kilts; Robert W. Buchanan; Eu Pui Wai; Swapna Verma; Kang Sim; Jayaraman Hariram; et al. (Psychopharmacology, 2014)

Expression of the Human Tissue-Plasminogen Activator in Hairy Roots of Oriental Melon (Cucumis melo) - Sol Kang; Hemavathi Ajjappala; Hyun-Hui Seo; Joon-Soo Sim; Sang-Hong Yoon; Bon-Sung Koo; Yong-Hwan Kim; Sukchan Lee; Bum-Soo Hahn (Plant Molecular Biology Reporter, 2011)

The complete genome sequence and molecular analysis of human hepatitis E virus genotype IV identified from a Korean patient - Haesun Yun; Jin Seon Kim; Hyeok Jin Lee; Sook Hyang Jeong; Jeong Sim Kim; Sang Jong Park; Seong Gyu Hwang; Sook Kyoung Kang; Youngmee Jee; Jong Hyun Kim (Archives of Virology, 2010)

Pseudomonas sp. LSW25R, antagonistic to plant pathogens, promoted plant growth, and reduced blossom-end rot of tomato fruits in a hydroponic system - Sang-Woo Lee; Il-Pyung Ahn; Sang-Yeon Sim; Sue-Yeon Lee; Myeon-Whoon Seo; Soonok Kim; Sook-Young Park; Yong-Hwan Lee; Seogchan Kang (European Journal of Plant Pathology, 2010)

Hairy root induction in Oriental melon (Cucumis melo) by Agrobacterium rhizogenes and reproduction of the root-knot nematode (Meloidogyne incognita) - Hyo-Kyung Pak; Joon-Soo Sim; Yong Rhee; Hyo-Rim Ko; Sun-Hwa Ha; Mun-Sup Yoon; Chan-Ho Kang; Sukchan Lee; Yong-Hwan Kim; Bum-Soo Hahn (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Direct extraction of astaxanthin from Haematococcus culture using vegetable oils - Chang Duk Kang; Sang Jun Sim (Biotechnology Letters, 2008)

Stabilization of papain and lysozyme for application to cosmetic products - Young-Chul Sim; Sung-Gu Lee; Dong-Cheol Lee; Byung-Young Kang; Kyung-Mok Park; Jang-Young Lee; Moo-Sung Kim; Ih-Seop Chang; Joon-Shick Rhee (Biotechnology Letters, 2000)

Light-independent regulation of chloroplast translation elongation factor tu gene expression in three types of grass: Rice, maize, and barley - II Ho Kang; Joong Won Lee; Jeong Hwan Lee; Chuj Joo Kang; Woong Seop Sim; Jeong -Kook Kim (Journal of Plant Biology, 1998)

Protein kinase C mediates the desensitization of CCh-activated nonselective cationic current in guinea-pig gastric myocytes - Young Chul Kim; Sung Joon Kim; Jae Hoon Sim; Jae Yeoul Jun; Tong Mook Kang; Suk Hyo Suh; Insuk So; K. W. Kim (Pflügers Archiv - European Journal of Physiology, 1998)

Gene expression of chloroplast translation elongation factor Tu during maize chloroplast biogenesis - Jeong Hwan Lee; Il Ho Kang; Kyu Lee Choi; Woong-Seop Sim; Jeong-Kook Kim (Journal of Plant Biology, 1997)